2021
DOI: 10.1242/jeb.242608
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure across immune challenge severities in a lizard: consequences for innate immunity, locomotor performance and oxidative status

Abstract: Reptiles, like other vertebrates, rely on immunity to defend themselves from infection. The energetic cost of an immune response is liable to scale with infection severity, prompting constraints on other self-maintenance traits if immune prioritization exceeds energy budget. In this study, adult male side-blotched lizards (Uta stansburiana) were injected with high (20 µg/g body mass), low (10 µg/g body mass), or control (0 µg/g body mass) concentrations of lipopolysaccharide (LPS) to simulate bacterial infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 85 publications
1
11
1
Order By: Relevance
“…Our results are notably contrary to similar research done on male side-blotched lizards (U. stansburiana), which found that male RMR decreased after immune challenges, with the largest decreases in wound and wound + LPS treatments (Smith et al, 2017). However, these unusual results are not representative of most literature, which generally supports the notion that animals facing immune challenges will increase metabolism (Hudson, Virgin, Kepas, et al, 2021;Lind et al, 2020;Martin et al, 2003;Nilsson et al, 2007). Moreover, these immune responses are dynamic and differences of timing in metabolic measurements could yield vastly different results.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are notably contrary to similar research done on male side-blotched lizards (U. stansburiana), which found that male RMR decreased after immune challenges, with the largest decreases in wound and wound + LPS treatments (Smith et al, 2017). However, these unusual results are not representative of most literature, which generally supports the notion that animals facing immune challenges will increase metabolism (Hudson, Virgin, Kepas, et al, 2021;Lind et al, 2020;Martin et al, 2003;Nilsson et al, 2007). Moreover, these immune responses are dynamic and differences of timing in metabolic measurements could yield vastly different results.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the energetic cost of mounting an immune response may trade off with performance. Lizards treated with the bacterial cell wall component lipopolysaccharide (LPS) to induce an immune response have reduced sprint speed, possibly due to altered energy balance favoring immune response (Hudson et al, 2021;Zamora-Camacho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the energetic cost of mounting an immune response may trade off with performance. Lizards treated with the bacterial cell wall component lipopolysaccharide (LPS) to induce an immune response have reduced sprint speed, possibly due to altered energy balance favoring immune response (Hudson et al, 2021 ; Zamora‐Camacho et al, 2014 ). However, in mammals the antimicrobial immune response induced by LPS is distinct from the response against macroparasites and involves proinflammatory type 1 responses (Annunziato et al, 2014 ; Ashley et al, 2012 ; Spellberg & Edwards, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most natural scenarios, hosts face pathogen infections which differ in intensity (e.g., doses and frequency of exposure, see Aiello et al, 2016), then experimental challenges using gradients of infection intensity allow us to evaluate variations in disease progression with a better representation of natural systems. However, only a limited number of studies use this approach in wild species (e.g., Butler et al, 2021; Hudson et al, 2021; Leon & Hawley, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…But in these situations, the variation in susceptibility and sickness progression associated with different degrees of infection may be missed (Leon & Hawley, 2017). Although some studies have explored milder infection intensities (e.g., Baze et al, 2011; Cutrera et al, 2022), which could be more relevant in an ecological and evolutionary context, only a limited number of ecoimmunological studies have assessed the effects of a gradient of antigen exposure in wild species (e.g., Armour et al, 2020; Butler et al, 2021; Hudson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%